2012
DOI: 10.1364/boe.3.002021
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying collagen structure in breast biopsies using second-harmonic generation imaging

Abstract: Quantitative second-harmonic generation imaging is employed to assess stromal collagen in normal, hyperplastic, dysplastic, and malignant breast tissues. The cellular scale organization is quantified using Fourier transform-second harmonic generation imaging (FT-SHG), while the molecular scale organization is quantified using polarization-resolved second-harmonic generation measurements (P-SHG). In the case of FT-SHG, we apply a parameter that quantifies the regularity in collagen fiber orientation and find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 39 publications
(37 reference statements)
6
89
0
Order By: Relevance
“…Collagen fibers orientation have been studied on ex vivo uterine cervial tissue with SHG [43] and breast tumor tissue with polarization-resolved SHG [44]. Tanaka et al found that skin burn tissue presents molten and fibrous structures of dermal collagen [41], which is consistent with our finding on Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Collagen fibers orientation have been studied on ex vivo uterine cervial tissue with SHG [43] and breast tumor tissue with polarization-resolved SHG [44]. Tanaka et al found that skin burn tissue presents molten and fibrous structures of dermal collagen [41], which is consistent with our finding on Fig.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, SHG is a popular technology that has gained a lot of attention more recently, and it is regularly being used for other softer tissues such as tendon [108], cartilage [112] or intervertebral disc [110]. However, similarly to PLM, SHG cannot be employed to quantitatively determine the collagen density and, hence, to derive the DO of the fibrils, but provides the in-plane [115] and/or out-of-plane [116] orientation in a semi-quantitative way [117].…”
Section: Polarized Second Harmonic Generation Imagingmentioning
confidence: 99%
“…These metrics provide additional information on the collagen ultrastructural characteristics that is complementary to the concentration and spatial distribution measures. Polarization-sensitive SHG microscopy has been previously applied to determine differences in normal and malignant breast tissue [8], models of ovarian cancer [9], and non-small cell lung carcinoma [7]. In this study, we use polarization-in, polarization-out (PIPO) SHG microscopy to investigate classical papillary thyroid carcinoma (cPTC) and follicular variant papillary thyroid carcinoma (FVPTC).…”
Section: Introductionmentioning
confidence: 99%